Permeability Factors in Focal and Segmental Glomerulosclerosis - Reiser, Jochen (2014)
Focal and segmental glomerulosclerosis (FSGS) represents a group of glomerular disorders, identified on kidney biopsy, that progress in the histopathologic pattern of sclerosis in parts of some glomeruli. Damage to podocytes usually marks the beginning of the disease, most evident in primary FSGS. In addition to genetic predisposition, there are many acquired causes that disturb normal podocyte homeostasis and allow for the development of FSGS. The aim of this review is to summarize recent findings of the most relevant circulating permeability factors that may serve as biomarkers of active primary idiopathic FSGS, and aid in the diagnosis and prediction of recurrent FSGS post-kidney transplantation.